Blocking pathogen transmission at the source: reservoir targeted OspA-based vaccines against Borrelia burgdorferi - Gomes-Solecki, Maria (Frontiers in Cellular and Infection Microbiology, 2014)
Control strategies are especially challenging for microbial diseases caused by pathogens that persist in wildlife reservoirs and use arthropod vectors to cycle amongst those species. One of the most relevant illnesses that pose a direct human health risk is Lyme disease; in the US, the Centers for Disease Control and Prevention recently revised the probable number of cases by 10-fold, to 300,000 cases per year. Caused by Borrelia burgdorferi, Lyme disease can affect the nervous system, joints and heart. No human vaccine is approved by the Food and Drug Administration. In addition to novel human vaccines, new strategies for prevention of Lyme disease consist of pest management interventions, vector-targeted vaccines and reservoir-targeted vaccines. However, even human vaccines can not prevent Lyme disease expansion into other geographical areas. The other strategies aim at reducing tick density and at disrupting the transmission of B. burgdorferi by targeting one or more key elements that maintain the enzootic cycle: the reservoir host and/or the tick vector. Here, I provide a brief overview of the application of an OspA-based wildlife reservoir targeted vaccine aimed at reducing transmission of B. burgdorferi and present it as a strategy for reducing Lyme disease risk to humans.